OPTIMASI POLA TANAM DAN ALOKASI INPUT UNTUK PENINGKATAN KETAHANAN PANGAN RUMAH TANGGA DI LAHAN PASANG SURUT KABUPATEN KUBU RAYA KALIMANTAN BARAT - Musyafak, Akhmad; Irham, .; Hartono, Slamet; Jamhari, . (Jurnal AGRISEP, 2011)
The research was conducted in the district of Kubu Raya which is focused on swamp land. The purpose of this study are (a) optimizing the allocation of cropping pattern and input to achieve household food security and income maximum, (b) to simulate changes in input prices and output and its impact on cropping patterns, household income, and allocation of inputs. Location selected by purposive sampling technique taking into account the typology of land and type of overflow, whereas the primary data collected from farm households by simple random sampling technique. Data were analyzed with linear programming and sensitivity analysis. An important result of this study are as follows: (1) Optimal cropping patterns in swamp lands are as follows: (a) the type of SMA / A, paddy field: rice - rice, (b) the type of SMP / A, paddy field: rice - rice, and dry land: coconut, (c) type SMP / B, paddy fields: corn-corn, and dry land: fruit, (d) the type of SMP / C, paddy field: rice-paddy and dry land: coconut, (e) type bergambut / B, wetland : paddy-rice, and dry Ahan: coconut, (f) type bergambut / C, paddy field: rice-paddy and dry land: coconut, (g) the type of peat is / B, the paddy field: rice-paddy, (h ) the type of shallow peat / D, wet land: paddy-rice, and dry land: rubber; (2)  the optimal allocation of inputs consisting of family labor 166.74 day of man work/year,  rent labor 132.74 day of man work/year, seed of paddy 70.54 kg/year, Urea 189.28 kg/year, SP36 94.34 kg/year, KCl 56.35 kg/year, NPK 75.66 kg/year, organic fertilizer 65.99 kg/year, herbicide 8.62 lt/year, dan pesticida 2.29 lt/year; (3) the actual household income of Rp 2,200,000.00 / household / year, if carried out optimization of unconditional “food patterns of national expectations/FPNE” increased to Rp 3,883,234.87 / household / year and if there is a requirement of the FPNE decreased to Rp 1,285,839.37 / household / year. (4) the price of rice and corn prices are most sensitive to fluctuations. If the price of rice rose more than 5% or the price of corn rose more than 50% (cateris paribus) the optimal solution will change. Likewise, if the price of rice fell by more than 34% or corn prices fell more than 9% (cateris paribus) the optimal solution will change. (5) The simulation results show that the rise in input prices and output prices 10% did not alter the optimal solution. But the impact on household income increased by 37.87% (unconditional FPNE), and 114.37% (provided FPNE). Simulated 10% decrease in output price and input prices fixed, it does not alter the optimal solution, but the impact on the decline in household income by 152.15% (unconditional FPNE) and 459.49% (provided FPNE). Keywords: optimize, farm household, swamp area, food security,